Electronic health literacy and demand for digital health technology among the elderly in Rajasthan - Ashok Kumar; Praveena Tandon; Gaurav Meratwal (Wolters Kluwer Medknow Publications, 2023)
Background: Older people may not be able to use information and communication technologies to get health care due to an age-related digital divide. This study aimed to evaluate the use of the Internet, eHealth literacy levels, and the demand for digital health technologies among the elderly. Materials and Methods: This hospital-based cross-sectional study was conducted from May 2022 to December 2022 in a tertiary care hospital in Ajmer. Three hundred and six elderly people aged 60 years or older and who visited the hospital were included in the study. Data were collected using a pretested, semi-structured, interviewer-administered questionnaire. Literacy in eHealth was evaluated using the electronic Health Literacy Scale (eHEALS). Multiple logistic and multiple linear regressions were used to predict the factors associated with smart device usage and eHealth literacy. Results: The mean (standard deviation [SD]) age of the participants was 69.47 (6.28) years. Approximately one-fifth (n = 61) of the elderly had used a smart device. All participants with smart devices (n = 61, 19.9%) were Web 2.0 users. The mean eHEALS score (SD) was 14.08 (8.81), and the median was 11 (interquartile range = 10). It ranged from 8 to 40. eHealth literacy was significantly associated with residence (B = 0.06, P < 0.01), education (B = 0.53, P < 0.01), income (B = 0.14, P < 0.01), and smartphone ownership (B = −0.41, P < 0.01). Conclusion: In India, Internet use and eHealth literacy are low among the elderly. The National Digital Health Mission is aimed at increasing access to health information through digital technology, but it is also important that older people have the ability to understand and evaluate the resources they find. Future research should focus on improving the use of the Internet by the elderly and the literacy of electronic health care and create interventions based on these areas.